The Effects of Rivalry on Rivalry: Accommodation and the Management of Threats1. Issue 1 (2nd May 2013) - Akcinaroglu, Seden; Radziszewski, Elizabeth; Diehl, Paul F.
Abstract : The paper investigates how states manage multiple rivalries when faced with immediate threats. We argue that accommodation of one rival allows states to shift resources from the management of another rival to deal with the costs of immediate threats. By examining enduring rivalries from 1966 to 1999, we show that states' reliance on accommodation in response to threats varies depending on the number of severe threats and the relative capabilities between the states and the threat‐issuing rivals. Findings show that when faced with severe but few threats, states prefer to accommodate rivals that did not issue the threat. They are also more likely to give larger concessions to such rivals and to those issuing less severe threats. Finally, the greater the military capability of a rival issuing a severe threat relative to that of the challenged state, the more likely that a threatening rival is accommodated.